2012
DOI: 10.1007/s10877-012-9335-3
|View full text |Cite
|
Sign up to set email alerts
|

Ability of the Masimo pulse CO-Oximeter to detect changes in hemoglobin

Abstract: The decision to administer blood products is complex and multifactorial. Accurate assessment of the concentration of hemoglobin [Hgb] is a key component of this evaluation. Recently a noninvasive method of continuously measuring hemoglobin (SpHb) has become available with multi-wavelength Pulse CO-Oximetry. The accuracy of this device is well documented, but the trending ability of this monitor has not been previously described. Twenty patients undergoing major thoracic and lumbar spine surgery were recruited.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 19 publications
(42 reference statements)
0
36
0
Order By: Relevance
“…This recently reviewed technique 1 has been used in studies involving volunteers and surgery, with varying conclusions about accuracy and precision. [2][3][4][5][6][7][8][9][10][11] However, little is known about how SpHb reacts to specific procedures performed during surgery, such as intravenous infusion of crystalloid and colloid fluid. There is some evidence that SpHb changes more than Hb during volume loading with Ringer's acetate 7 but no evaluation of the accuracy of SpHb during administration of colloid fluid has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…This recently reviewed technique 1 has been used in studies involving volunteers and surgery, with varying conclusions about accuracy and precision. [2][3][4][5][6][7][8][9][10][11] However, little is known about how SpHb reacts to specific procedures performed during surgery, such as intravenous infusion of crystalloid and colloid fluid. There is some evidence that SpHb changes more than Hb during volume loading with Ringer's acetate 7 but no evaluation of the accuracy of SpHb during administration of colloid fluid has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy and reliability of the portable Pronto-7 Pulse COOximeter was reported in numerous studies conducted in the operating room [10][11][12][13][14][15][16][17][18][19][20][21] and in the intensive care unit [4,5,[22][23][24][25] with predominantly satisfactory performance. In a study done in bleeding trauma patients the agreement was moderate [bias (LOA) of -0.6 (-3.0; +1.9)] g/dl [26], where the limit of agreement is defined as the mean difference + twice the standard deviation of the differences [27].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only a few studies have evaluated these devices' trending ability (Table 2) [10,24,[31][32][33]. Four studies have shown …”
Section: Trending Ability Of Noninvasive Hemoglobin Monitoringmentioning
confidence: 99%
“…To this point, a four-quadrant plot analysis is inadequate as this analysis simply provides the directionality of the Hb changes. Colquhoun et al[31] assessed the tracking ability using a polar plot analysis and found a good agreement with the concordance rate of 90%, whereas Giraud et al[32] reported a poor agreement with angular bias and SD of À17.38 AE 19.28. It is worth mentioning that most of the studies evaluating the NIHb tracking ability simply compared Hb values between two time points and did not include any clinical interventions, such as volume expansion or transfusion.…”
mentioning
confidence: 99%